A novel adjuvant system BK-02 with CpG2006 and MF59 enhances the immunogenicity of a herpes zoster subunit vaccine - Wang, Zihan; Guo, Yingnan; Tang, Xin; Sun, Ying; Wu, Tingting; Peng, Hanyu; Wang, Cenrong; Su, Weiheng; Jiang, Chunlai; Zang, Yang; Quan, Yaru; Xu, Kangwei; et al. (Frontiers in Immunology, 2025)
IntroductionReactivation of the varicella-zoster virus (VZV) results in herpes zoster (HZ), which can lead to complications such as postherpetic neuralgia. The commercially available HZ subunit adjuvanted vaccine, Shingrix®, offers significant protection against HZ in older adults. However, the adjuvant system of this vaccine has limitations that necessitate the development of alternative adjuvant systems.MethodsIn this study, we established a novel adjuvant system, BK-02, composed of both the Toll-like receptor 9 (TLR9) agonist BK-02C (CpG2006) and a squalene-based oil-in-water emulsion, BK-02M (MF59), using ELISA, ELISpot, and flow cytometry analyses. ResultsOur results showed that when combined with glycoprotein E (gE), the active ingredient of a recombinant HZ vaccine, the BK-02 adjuvant system elicited significantly higher gE-specific IFN-γ+ T-cell responses (486 SFU/10⁶ cells, 121-fold increase vs gE alone) and IgG antibody titers (Lg titers 5.2 vs 3.4 for gE alone). The optimal dose (5 μg gE + 30 μg BK-02C + 1× BK-02M) for inducing gE protein-specific cellular immunity was determined in mice. This corresponded to a clinical dose of “50 μg gE + 300/500 μg BK-02C + 0.5 mL BK-02M.” Additionally, pilot-scale samples of the recombinant HZ vaccine demonstrated enhanced gE-specific CD4+ and CD8+ T-cell immune responses, compared to Shingrix®. Moreover, the gE/BK-02 adjuvant system induced a Th1-regulated mixed immune response, enabling robust cellular and humoral immunity. DiscussionThese findings indicated that the BK-02 adjuvant system is a promising adjuvant candidate for the current HZ subunit vaccines.